A national survey of out‐of‐hours working and fatigue in consultants in anaesthesia and paediatric intensive care in the UK and Ireland. (2nd September 2019) - McClelland, L.; Plunkett, E.; McCrossan, R.; Ferguson, K.; Fraser, J.; Gildersleve, C.; Holland, J.; Lomas, J. P.; Redfern, N.; Pandit, J. J.
Summary: The tragic death of an anaesthetic trainee driving home after a series of night shifts prompted a national survey of fatigue in trainee anaesthetists. This indicated that fatigue was widespread, with significant impact on trainees' health and well‐being. Consultants deliver an increasing proportion of patient care resulting in long periods of continuous daytime duty and overnight on‐call work, so we wished to investigate their experience of out‐of‐hours working and the causes and impact of work‐related fatigue. We conducted a national survey of consultant anaesthetists and paediatric intensivists in the UK and Ireland between 25 June and 6 August 2018. The response rate was 46% (94% of hospitals were represented): 84% of respondents (95%CI 83.1–84.9%) contribute to a night on‐call rota with 32% (30.9–33.1%) working 1:8 or more frequently. Sleep disturbance on‐call is common: 47% (45.6–48.4%) typically receive two to three phone calls overnight, and 48% (46.6–49.4%) take 30 min or more to fall back to sleep. Only 15% (14.0–16.0%) reported always achieving 11 h of rest between their on‐call and their next clinical duty, as stipulated by the European Working Time Directive. Moreover, 24% (22.8–25.2%) stated that there is no departmental arrangement for covering scheduled clinical duties following a night on‐call if they have been in the hospital overnight. Overall, 91% (90.3–91.7%) reported work‐related fatigue with over half reporting a moderate or significantly negative impact on health, well‐being and home life. We discuss potential explanations for these results and ways to mitigate the effects of fatigue among consultants.